2015
DOI: 10.1371/journal.pone.0116540
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases Airway Hyperresponsiveness via the TNF-α Pathway and Treating Obesity Induces Recovery

Abstract: Obesity is a known risk factor for allergic asthma. It has been recognized as a key player in the pathogenesis of several inflammatory disorders via activation of macrophages, which is also vital to the development of allergic asthma. We investigated the mechanism of obesity-related asthma and whether treating obesity through exercise or diet ameliorates the severity of asthma in the obesity-related asthma model. We generated diet-induced obesity (DIO) in C57BL/6 mice by high-fat-feeding and ovalbumin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
1
40
0
2
Order By: Relevance
“…Our results showed an efficient induction of bronchial asthma evidenced by significant and massive reductions in the respiratory functions TV and PEFR (table 1), which agreed with previous investigations in rats and mice [35,36,37]. Cytokines, particularly TNF-α, are involved in the initiation and progression of airway inflammation [38,39], with IL-5 particularly reported to have a central role in the initiation of eosinophilic airway inflammation [40], strongly agreeing with our results (table 2). IgE plays a key role in the pathogenesis of extrinsic asthma, as in our model (table 3), through stimulating mast cell degranulation [41].…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed an efficient induction of bronchial asthma evidenced by significant and massive reductions in the respiratory functions TV and PEFR (table 1), which agreed with previous investigations in rats and mice [35,36,37]. Cytokines, particularly TNF-α, are involved in the initiation and progression of airway inflammation [38,39], with IL-5 particularly reported to have a central role in the initiation of eosinophilic airway inflammation [40], strongly agreeing with our results (table 2). IgE plays a key role in the pathogenesis of extrinsic asthma, as in our model (table 3), through stimulating mast cell degranulation [41].…”
Section: Discussionsupporting
confidence: 91%
“…TNF-is a pleiotropic cytokine that upregulates the expression of adhesion molecules, cytokines, and chemokines in the bronchial mucosa of patients with asthma, implicating an important role for TNF-in the pathogenesis of severe asthma 13,14 . Recent data also showed that TNFinhibits eosinophil apoptosis 15 , and that the TNF-pathway could be associated with airway hyper-responsiveness in obesity, one of the risk factors for the severity of asthma 16 . The exact mechanistic relationship between airway remodeling and TNF-has not been clari ed ; however, it is possible that endothelin-1, induced In turn, TGFis a multifunctional cytokine that exerts many biological effects including immunosuppressive and in ammation-regulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Uyku sırasında parasempatik tonüs artışı sabaha karşı bronkodilatör tonüs azalması, kortikosteroid ve katekolamin seviyelerinde gece boyunca azalma olması da noktürnal astım gelişimine yol açmaktadır (26). Obstrüktif apne OSAS'lı olgularda görülen hipoksemi karotis cisimciklerinin stimülasyonu yolu ile refleks bronkospazma yol açar (26,27). Hava yolu çapındaki belirgin azalma OSAS'lılarda sıklıkla görülen müller manevrası ile vagus stimülasyonuna sebep olur; bu durum hava yolu hastalığını provake eder.…”
Section: Discussionunclassified
“…OUAS'lı hastalarda hava yollarında gelişen lokal enflamasyon hava yolu çapı değişikliğine yol açtığı gibi bronşial hiperaktivite ve bronş spazmını da tetiklemektedir (26). Astımlı hastalarda OUAS sıklığının yüksek olması rinite bağlı nasal konjesyon, nasal obstrüksiyon, atopiye bağlı polipler, obeziteye bağlı farenkste artmış yağ dokusu, noktürnal semptomlara bağlı uyku bozukluğu gibi mekanizmalarla açıklanmıştır (27). Çalışmamızda, 970 OUAS tanısı konulan hastanın 59'unda (%5,6) astım mevcuttu.…”
Section: Discussionunclassified